## What is a3 minus b3?

a3 – b3 = (a – b) (a2 + ab + b2 ). 9. a3 + b3 = (a + b) (a2 – ab + b2 ). 10.

## What is the formula of a cube minus B cube?

We already know the formula/expansion for (a – b)3. Add 3ab(a – b) to each side. are the factors of (a3 – b3).

## What is a cube plus B cube formula?

In this section, you will learn the formula or expansion for (a3 + b3). We already know the formula/expansion for (a + b)3. That is, (a + b)3 = a3 + b3 + 3ab(a + b)

## What is the formula of a³ B³?

a³-b³= (a-b)(a²+ab+ b²) is the formula. Expressed in words, the difference of the cubes of two quantities is the product of the difference of the two quantities by the “imperfect square of the sum.”

## How do you prove a3 b3?

Prove a3-b3=(a-b)(a2+b2+ab) by activity =>a3+b3+3ab(a+b)=(a+b)2 (a+b) =>a3+b3=(a+b)2 (a+b) – 3ab(a+b) =(a+b) {(a+b)2-3ab} =(a+b)(a2+b2+2ab-3ab) =(a+b)(a2+-ab+b2) verified.

## What is the formula of cube?

Cube and Cuboid Formulas

Cube Cuboid
Total Surface Area = 6(side)2 Total Surface area = 2 (Length x Breadth + breadth x height + Length x height)
Lateral Surface Area = 4 (Side)2 Lateral Surface area = 2 height(length + breadth)
Volume of cube = (Side)3 Volume of the cuboid = (length × breadth × height)

## What is a³ +B³?

Difference of two squares: a² – b² = (a+ b)(a – b) Sum of two cubes: a³ + b³ = (a + b)(a² – ab + b²) Difference of two cubes: a³ – b³ = (a – b)(a² + ab + b²) Memorizing these formulas will help you solve quadratic equations quickly. …

## What are the factors of a3 b3?

Answer: An expression of the form a3 + b3 is called a sum of cubes. The factored form of a3 + b3 is (a + b)(a2 – ab + b2): (a + b)(a2 – ab + b2) = a3 + a2b – a2b – ab2 + ab2 + b3 = a3 – b3.

## What is cube and example?

The definition of a cube is a three-dimensional square with six equal sides. An example of a cube is a piece of cheese with six square sides. An example of a cube is a piece of ice. To cube is to cut something into a three-dimensional square.

## What is the formula for a cube minus B Cube?

The a 3 – b 3 formula is also known as one of the important algebraic identiy. It is read as a cube minus b cube. Its a 3 – b 3 formula is expressed as a 3 – b 3 = (a – b) (a 2 + ab + b 2 ).

## How to find the value of a minus B?

Substitute x for a and 1 for b. Write the formula / expansion for (a – b)3. Substitute 2x for a and 3 for b. Write the formula / expansion for (a – b)3. Substitute x for a and 2y for b. If a – b = 3 and a3 – b3 = 1197, then find the value of ab. To find the value of ab, we can use the formula or expansion for (a – b)3.

## What is the formula for a 3-B 3?

What is a^3-b^3 Formula? The a 3 – b 3 formula can be verified, by multiplying (a – b) (a 2 + ab + b 2) and see whether you get a 3 – b 3. The a 3 – b 3 formula or the difference of cubes formula is explained below: a 3 – b 3 = (a – b) (a 2 + ab + b 2)

What is a3 minus b3? a3 – b3 = (a – b) (a2 + ab + b2 ). 9. a3 + b3 = (a + b) (a2 – ab + b2 ). 10. What is the formula of a cube minus B cube? We already know the formula/expansion for (a – b)3. Add 3ab(a –…